Tracing the path of Yoga : the history and philosophy of Indian mind-body discipline - Sarbacker, Stuart Ray, 1969- (State University of New York Press, 2021)
A comprehensive and theory-rich investigation of the history and philosophy of yoga, from its Indian origins to the contemporary context. Clear, accessible, and meticulously annotated, Tracing the Path of Yoga offers a comprehensive survey of the history and philosophy of yoga that will be invaluable to both specialists and to nonspecialists seeking a deeper understanding of this fascinating subject. Stuart Ray Sarbacker argues that yoga can be understood first and foremost as a discipline of mind and body that is represented in its narrative and philosophical literature as resulting in both numinous and cessative accomplishments that correspond, respectively, to the attainment of this-worldly power and otherworldly liberation. Sarbacker demonstrates how the yogic quest for perfection as such is situated within the concrete realities of human life, intersecting with issues of politics, economics, class, gender, and sexuality, as well as reflecting larger Indic religious and philosophical ideals